Prevention and therapy of preterm birth: guideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF registry number 015/025, September 2022) : part 1 with recommendations on the epidemiology, etiology, prediction, primary and secondary prevention of Preterm birth = Prävention und Therapie der Frühgeburt : Leitlinie der DGGG, OEGGG und SGGG (S2k-Level, AWMF-Registernummer 015/025, September 2022) : Teil 1 mit Empfehlungen zur Epidemiologie, Ätiologie, Prädiktion, primären und sekundären Prävention der Frühgeburt - Berger, Richard; Abele, Harald; Bahlmann, Franz; Doubek, Klaus; Felderhoff-Müser, Ursula; Fluhr, Herbert; Garnier, Yves; Grylka-Baeschlin, Susanne; Hayward, Aurelia; Helmer, Hanns; Herting, Egbert; Hoopmann, Markus; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Aim: This revised guideline was coordinated by the German Society for Gynecology and Obstetrics (DGGG), the Austrian Society for Gynecology and Obstetrics (OEGGG) and the Swiss Society for Gynecology and Obstetrics (SGGG). It aims to improve the prediction, prevention, and management of preterm birth, based on evidence from the current literature, the experience of members of the guidelines commission, and the viewpoint of self-help organizations. Methods: The members of the contributing professional societies and organizations developed recommendations and statements based on international literature. The recommendations and statements were presented and adopted using a formal process (structured consensus conferences with neutral moderation, written Delphi vote). Recommendations: Part 1 of this short version of the guideline presents statements and recommendations on the epidemiology, etiology, prediction, and primary and secondary prevention of preterm birth.